Comparison of Knowledge and Attitudes Regarding Free Sexual Behavior Among Male and Female University Students - Yuanita Ani Susilowati; Emanuel Ade Nugraha; Ferdinan Sihombing; Yosi Maria Wijaya; Stepanus Prihasto Septiawan; Dian Putrawangsa (Journal of Health and Nutrition Research, 2026)
Free sexual behavior among adolescents encompasses activities such as hugging, kissing, and intercourse, which are influenced by knowledge and attitudes. This issue is particularly concerning among university students, who are at a developmental stage characterized by heightened sexual drive. This study aimed to analyze differences in knowledge and attitudes toward free sexual behavior between male and female university students. A comparative quantitative study was conducted using a convenience sampling technique involving 398 students aged 18–25 from a private university in Bandung. Data were collected through a validated and reliable questionnaire consisting of 15 knowledge questions and 15 attitude questions. The Mann–Whitney test was used to assess the differences in average scores between the groups. The results showed that female students had higher average scores in both knowledge (Mean = 9.77 vs. 9.18; p = 0.009) and attitudes (Mean = 49.12 vs. 44.02; p < 0.000) compared to male students. Only a small proportion of students had good knowledge, and most male students exhibited negative attitudes, indicating approval or willingness to engage in such behavior. These findings suggest that knowledge and attitudes play a critical role in shaping sexual behavior among university students.  These findings underscore the urgency of developing gender-responsive sexual health education interventions in higher education settings.